Analisis Waktu Kerja untuk Penentuan Kebutuhan Tenaga Kerja dalam Memenuhi Permintaan di CV. Barokah Metal Sidoarjo - Ramadhaniyah, Nayla Ayu; Satoto, Handy Febri (Fakultas Teknik UMRI, 2025)
CV. Barokah Metal is a business engaged in the motorcycle spare parts manufacturing industry in the form of planers. Every day it is targeted to produce 60 dozen. However, sometimes consumer demand cannot be met. One of the reasons for not meeting the target is influenced by the performance and consistency of each worker, so it is necessary to determine the standard time using the stopwatch time study method in order to maximize workers in completing their work. After calculating, the standard time for operator 1 was 34.17 seconds, operator 2 33.89 seconds, operator 3 11.49 seconds, operator 4 38.96 seconds, operator 5 7.66 seconds, operator 6 46.40 seconds, operator 7 25.39 seconds, operator 8 33.17 seconds, and operator 9 60.45 seconds. The number of workers needed to meet the demand is 12 people, by adding 1 worker each for operator 4, operator 6 and operator 9.